A meta-analysis of the relationship between polycystic ovary syndrome and sleep disturbances risk - Wang, Chaoyu; Huang, Tao; Song, Wu; Zhu, Jinru; Liu, Yanhong; Chen, Xiaojuan; Sun, Xishi; Wu, Qinglan; Chen, Huimin; Liao, Huizhao; Lin, Junyan; Ou, Xudong; et al. (Frontiers in Physiology, 2022)
Objective: A meta-analysis is used to explore the relationship between polycystic ovary syndrome (PCOS) and the risk of Sleep disturbances. Method: Cochrane Library, PubMed, Embase, and Web of Science databases are searched by computer from their establishment to May 1st, 2022. Manage 5.4.1 software is used for the meta-analysis. Results: A total of nine articles are included, with 1,107 subjects. The results show that PCOS is positively associated with the risk of Sleep disturbances. Comparing with the "PCOS group" (experimental group) with the "NON-PCOS group" (control group), the incidence of Sleep disturbances is higher (OR = 11.24, 95% CI: 2.00–63.10, Z = 2.75, P = 0.006); the PSQI score of the PCOS group is higher than that of the NON-PCOS group (MD = 0.78, 95% CI: 0.32–1.25, Z = 3.30, P = 0.001); the ESS score of the PCOS group is higher than that of the NON-PCOS group (MD = 2.49, 95% CI: 0.80–4.18, Z = 2.88, P = 0.004); AHI events in the PCOS group are higher than those in the NON-PCOS group (MD = 2.68, 95% CI: 1.07–4.28, Z = 3.27, P = 0. 001); the sleep efficiency of the PCOS group is lower than that of the NON-PCOS group (MD = -5.16, 95% CI: -9.39–-0.93, Z = 2.39, P = 0.02); the sleep onset latency of the PCOS group is higher than that of the NON-PCOS group (MD = 2.45, 95% CI: 1.40–3.50, Z = 4.57, P < 0.001); and REM sleep in the PCOS group is higher than that in the NON-PCOS group (MD = 17.19, 95% CI: 11.62–55.76, Z = 6.05, P < 0.001). The studies included in each analysis have publication biases of different sizes. After subgroup analysis and sensitivity analysis, the heterogeneity of each study in the meta-analysis is reduced, the bias is reduced accordingly, and the stability of the results can be maintained.